Covid-19 negatively impacted on small oncology surgery but none on major procedures: Regional experience. (January 2022) - D'Ascanio, Luca; Latini, Gino; Pandolfini, Manlio; Imperatori, Luca; Di Stadio, Arianna; ,
Highlights: Covid-19 negatively impacted on surgery reducing the number of patients treated. Tardive cancer treatment can increase the mortality rate especially in head and neck malignancies. Relocation of department and creation of totally COVID-free hospitals can allow to maintain excellent patients' care. Our region created a free-COVID hospital during pandemic allowing us to preserve standard care. Abstract: Aim: To understand the impact of COVID pandemic on the activity and patients' care of the Head and Neck regional Unit, temporary moved in a COVID-free hospital. Methods: We retrospectively analyzed the yearly activity of the "Head & Neck Cancer Unit" at the Azienda Ospedali Riuniti Marche Nord (Italy) during 2020 (COVID-19 pandemic) and we compared it with the one performed in 2019. Statistical analyses were performed using Chi-square. Results: No significant differences were observed comparing the total number of patients treated for H&N squamous cell carcinoma (SCC) in 2019 with the ones in 2020. Moreover, no differences were identified in term of cancer stage at the moment of the surgery between 2019 and 2020. On the contrary, a significant reduction in the number of surgical procedures carried out for thyroid (p < 0.05) and skin (p < 0.001) malignancies was identified. Conclusions: Despite Covid-19 limitations, our institution was able to preserve the number of major oncologic procedures without negative impact on patients' care. We believe that the creation of specific COVID-free hospital can be the key preserve quality of care in epidemic emergency.